Structural Change under New Labour. - Coutts, K; Glyn, A; Rowthorn, B (Department of Economics (University of Oxford), 2007)
The decline in the importance of tradeable goods production in providing employment has continued in the past decade; distribution, public serices and business and financial services all provide more jobs than tradeable goods. Manufacturing output has stragnated under New Labour despite rapid growth of expenditure on manufactures. The result has been a sharp deterioration in the trade balance in manufactures. However the current account has only been in modest deficit shielded by additional net exports from finance and business services, higher earnings on overseas investments and an improvement in the terms of trade. The North of the country lost more industrial jobs than the South, but since 2000 the North has seen a greater expansion of jobs in public services and also finance and business services. Combined with a slower growth of population this has implied that the employment rate has actually risen in the North as compared to the South - a striking reversal of a long running trend. The government has taken a relaxed attitude to the decline in manufacturing over the past decade and has played down the importance of deliberate policies to bring jobs to the most affected regions. Paradoxically the major reason for the recent narrowing of the regional employment gap in recent years has been the very rapid expansion of jobs linked directly to public spending.